Siamese twins with craniofacial duplication and bilateral cleft lip/palate in a ceramic representation of the Chimú culture (Peru): a comparative analysis with a current case. (2014)
Craniofacial duplication or diprosopus is a very rare malformation that is present in approximately 0.4% of conjoined twins. Here is presented a case of craniofacial duplication in association with bilateral cleft lip/palate in both heads found in a ceramic representation from the early Chimú culture from Peru. A comparative analysis is made with a current case of a 28-week-old fetus with similar characteristics. After reviewing the medical literature on conjoined twins, very few reports of facial cleft in both twins were found, with no reports at all of bilateral cleft lip/palate. This ceramic crock is considered one of the first representations suggestive of craniofacial duplication, and probably the first reporting it in association with facial cleft.